Deselularisasi Makroalga Eucheuma cottonii dan Ulva sp. sebagai Bahan Dasar Perancah untuk Rekayasa Jaringan - I Kadek Adi Aryatama; Komang Trisna Sumadewi; Fransiscus Fiano Anthony Kerans (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Scaffold fabrication is an essential component in tissue engineering which is important in the field of biomedicine and regenerative health therapy. One of the scaffold fabrication methods is tissue deselularization method. In general, deselularization methods use animal organ as the base material. However, a number of studies in recent years have explored the potential of cellulose-based tissue engineering scaffolds from macroalgae. Macroalgae Eucheuma cottonii and Ulva sp. are seaweed species with high cellulose content and high abundance in Indonesia. Therefore, this study aims to determine whether macroalgae Eucheuma cottonii and Ulva sp. can be desulphurized by physico-chemical methods using the immersion-agitation technique of samples in Triton X-100 solution to be used as biological scaffolds. The research method used was an experimental research method divided into control and treatment groups consisting of Triron X-100 concentration variations, namely 0.1%, 0.5%, and 1%. The results of this study showed that the successful deselularization of Eucheuma cottonii using Triton X-100 solution with a concentration of 0.5% and 1% for 10 days was able to provide a clear transparent macroscopic picture and a microscopic picture of the loss of cell nuclei by maintaining the cell wall structure. However, the three concentrations of Triton X-100 could not desulphurize the macroalgae Ulva sp. Testing the pore characteristics of the scaffold, biodegradability test, and biocompability test still need to be done to evaluate the success of this macroalgae-based scaffold so that it can be utilized in tissue engineering.